Challenges and opportunities for the development of future teachers’ professional competence in Latvia - Āboltiņa, Līga; Lāma, Gatis; Sarva, Edīte; Kaļķe, Baiba; Āboliņa, Anda; Daniela, Linda; Rubene, Zanda; Bernande, Māra (Frontiers in Education, 2024)
In the 21st century, characterised by the continual evolution of education and new educational needs being raised and demanded, teachers’ professional competence encounters a series of challenges. In the context of Latvian education, it is highly significant to enhance the professional competence of future teachers and adapt it according to real-world challenges and opportunities. The professional competence of future teachers encounters challenges ranging from adapting to technological advancements to fostering an inclusive learning environment for diverse groups of students. In this research mixed method approach is applied, quantitative data from the self-evaluation instrument developed through the project “Development and Implementation of the Education Quality Monitoring System” (2nd round) and qualitative data from focus group discussions with education stakeholders are employed to analyse the challenges and opportunities for the development of future teachers’ professional competence. Based on the analysis, challenges for the enhancement of future teachers’ professional competence were identified at both institutional and individual levels amongst those strengthening schools as learning organisations and fostering open mindset towards change. By shedding light on these challenges and opportunities, this study contributes to the broader discourse on teachers’ preparation and continuous development, ensuring their readiness to navigate the multifaceted landscape of modern education effectively.